What increases the urban–rural gap in firm entry rates? - Kim, Younjun; Orazem, Peter (Small Business Economics, 2025)
Keywords: Agglomeration; Business; Economic geography; Economics; Entrepreneurship; Finance; Firm entry; Human capital; J24; M13; R11; Rural; Urban; dept.eco; peer-reviewed

Routine-biased technological change and declining employment rate of immigrants - Kim, Younjun; Thompson, Eric (Eastern Economic Journal, 2021)
We find that routine-biased technological change decreases the employment-to-population ratio of foreign-born population over the last three decades (1980–2010). This impact is greater for foreign-born population with lower English proficiency. As computerization and automation substitute for workers in routine occupations, switching from routine jobs to non-routine cognitive jobs may be more challenging for foreign-born workers than for native workers. © 2021, EEA.
Keywords: dept.eco

Overconfidence and Public Intoxication Arrest: Evidence from a University Town Police Log - Hoffman, Elizabeth; Kim, Younjun (The B.E. Journal of Economic Analysis & Policy, 2022)
We show that overconfident individuals are likely to be arrested for public intoxication by using arrest records from a university town police log. This relationship is robust to various control variables such as risk aversion, time discounting, present bias, self-control, selfishness, loss aversion, and socializing with peers arrested for public intoxication. However, this relationship is no longer significant using only self-reported arrest data. We hypothesize that overconfident individuals are likely to underreport their arrests. This result has important implications for the use of self-reported data on public intoxication arrests rather than actual arrest records.
Keywords: arrest; dept.eco; overconfidence; public intoxication

Testing for Consistency in Firm Entry and Exit Between the National Establishment Time Series and Business Dynamics Statistics - Kim, Donghyuk; Kim, Younjun; Orazem, Peter; Thomas, Kelsey (Growth and Change, 2026)
Keywords: Business statistics; Census; Consistency (knowledge bases); Dynamics (music); Longitudinal data; Series (stratigraphy); Time series; dept.eco; entrepreneurship; entry; exit; firm data

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

Bilateral environmental aid under trade competition - Yoon, Sang; Kim, Younjun; Park, Byoung; Yoon, Chang-Ho (Applied Economics Letters, 2026)
Keywords: Bilateral environmental aid; Bilateral trade; Competition (biology); Environmental impact assessment; Environmental policy; Trade barrier; climate finance; dept.eco; energy-saving aid; strategic aid allocation; trade competition

Which Small Towns Attract Start-Ups and Why? Twenty Years of Evidence from Iowa - Artz, Georgeanne M.; Kim, Younjun; Orazem, Peter F.; Han, Peter J. (American Journal of Agricultural Economics, 2021)
Using data on a sample of small Iowa towns consistently collected over two decades, we investigate how agglomeration economies, social capital, human capital, local fiscal policy, and natural amenities affect new firm entry. We find that human capital and agglomeration are more conducive to new firm entry than are natural amenities, local fiscal policy, or social capital. The impact of local fiscal policy is too small to overcome the locational disadvantages from insufficient endowment of human capital and agglomeration. A rural development approach that encourages firm entry in rural towns with the largest endowments of human capital and market agglomeration would be more successful than trying to raise firm entry in every town.
Keywords: M13; R11; R39; agglomeration; dept.eco; firm location; human capital; peer-reviewed; rural